1998
DOI: 10.1016/s0014-5793(98)00102-1
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of ecto‐ATPase and extracellular ATP in polymorphonuclear granulocyte‐endothelial interactions

Abstract: The adhesion of human polymorphonuclear granulocytes (PMN) with confluent human endothelial cells (line EAhy926) and with solid substrate coated by collagen and fibronectin (Fn) was studied by phase contrast microscopy and by the measurement of myeloperoxidase activity. The ecto-ATPase inhibitors suramin and Reactive Blue 2 (RB2) more than doubled the adhesion of PMN to endothelial cells. The cells hydrolyzed added ATP and this reaction was inhibited by suramin and RB2. The degree of ATP hydrolysis during PMN … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
12
0

Year Published

2001
2001
2014
2014

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 42 publications
3
12
0
Order By: Relevance
“…Extracellular ATP (eATP) influences T-cell activation (224, 225) and proliferation (226, 227), promotes neutrophil/endothelial cell adhesion (228), degranulation (229, 230), and reactive oxygen species (ROS) production (231), as well as other pro-inflammatory immune cell functions (232). eATP is transported to the extracellular space by vesicular trafficking, secreted via pannexin-1 channels (233), or released in large quantities from necrotic cells.…”
Section: Purinesmentioning
confidence: 99%
“…Extracellular ATP (eATP) influences T-cell activation (224, 225) and proliferation (226, 227), promotes neutrophil/endothelial cell adhesion (228), degranulation (229, 230), and reactive oxygen species (ROS) production (231), as well as other pro-inflammatory immune cell functions (232). eATP is transported to the extracellular space by vesicular trafficking, secreted via pannexin-1 channels (233), or released in large quantities from necrotic cells.…”
Section: Purinesmentioning
confidence: 99%
“…187,188 Of course, it cannot be excluded that the ATP effect could be at least in part mediated by its hydrolysis to adenosine, 189 but recent data suggest that ecto-ATPase activity has an inhibitory rather than stimulatory effect on granulocyte-endothelium interaction. 190 Dubyak and coworkers reported that chronic stimulation with ATP␥S or UTP could drive differentiation of myelomonocytic progenitor cells (HL-60 and U937). 191 Later studies showed that myeloid progenitors express P2Y 1 at earlier and P2Y 2 at later stages of differentiation.…”
Section: P2 Receptors In Polymorphonuclear Granulocytesmentioning
confidence: 99%
“…After 30 min of incubation with or without the additives in a CO 2 incubator at 37°C to allow neutrophil adherence, wells were washed twice with 500 µl of PBS solution for removal of nonadherent PMNLs. The extent of adherence was measured after the addition of detergent and a myeloperoxidase substrate, as described (Schierwagen et al, 1990;Sud'ina et al, 1998). A solution (300µl) of 5.5mM o-phenylenediamine and 4mM H 2 O 2 in buffer (67mM Na 2 HPO 4 , 35mM citric acid and 0.1% Triton X-100, pH5) was added to each well, and after 5 min the reaction was stopped by the addition of an equal volume of 1M H 2 SO 4 .…”
Section: Pmnl Adhesion Assaymentioning
confidence: 99%